2016
DOI: 10.1590/2179-8087.007115
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e Divergência Genética de Populações de Casearia grandiflora no Cerrado Piauiense

Abstract: RESUMOCasearia grandiflora (Salicaceae) é uma espécie típica do cerrado piauiense, o conhecimento da diversidade genética dessa espécie é de grande importância para estabelecimento de práticas e estratégias de conservação biológica. O presente estudo teve como objetivo caracterizar a diversidade de C. grandiflora em duas áreas de cerrado do Piauí. Foram analisados 15 descritores de natureza quantitativa, através da medição do caule, folha, fruto e semente, seguida de posterior análise multivariada (componentes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 11 publications
0
15
0
2
Order By: Relevance
“…The same group formation was confirmed by both the Tocher's method, based on the generalized distance of Mahalanobis (Table 4), and the canonical variables (Figure 1), for the biometric characteristics of fruit and seed of paradise nut genotypes. In a diversity study of Casearia grandiflora (Salicaceae), both the main component analysis and the clustering methods showed similarities in the clustering of the plants, which contributed to the knowledge of the phenotypic variation and divergence patterns of the species (Costa et al, 2016). In the present study, there was a large group separation due to their heterogeneity, which is of interest for breeding programs using distant genotypes.…”
Section: Resultsmentioning
confidence: 51%
“…The same group formation was confirmed by both the Tocher's method, based on the generalized distance of Mahalanobis (Table 4), and the canonical variables (Figure 1), for the biometric characteristics of fruit and seed of paradise nut genotypes. In a diversity study of Casearia grandiflora (Salicaceae), both the main component analysis and the clustering methods showed similarities in the clustering of the plants, which contributed to the knowledge of the phenotypic variation and divergence patterns of the species (Costa et al, 2016). In the present study, there was a large group separation due to their heterogeneity, which is of interest for breeding programs using distant genotypes.…”
Section: Resultsmentioning
confidence: 51%
“…The preponderance of genetic variation within populations in relation to variation between them is observed in several tree species for different phenotypic characteristics (Fernandes, 2008;Silva et al, 2012;Costa et al, 2016;Soares et al, 2017). These observations are also confirmed by studies carried out with the pequi tree in regions of northern Minas Gerais, where it was found that divergences among populations or between groups of populations for this species are relatively low (Melo Júnior et al, 2004;Fernandes, 2008).…”
Section: Discussionmentioning
confidence: 73%
“…Intrapopulational genetic divergence has also been observed through morphometric descriptors in Casearia grandiflora Camb. populations, with most of the variations being observed within the populations (COSTA et al, 2016).…”
Section: Intrapopulation Genetic Divergencementioning
confidence: 99%